Uso de álcool e tabaco entre universitários de Terapia Ocupacional de uma universidade pública - Pinho, Marina Coelho de (2018)
The use of psychoactive substances (SPAs) among university students deserves attention, especially alcohol and tobacco, due to the greater prevalence of users and greater social acceptance. Thus, the objective of the present study was to outline the profile of alcohol and tobacco use and its associated factors among university students of the Occupational Therapy course of a public university. This is a crosssectional and quantitative study. The research instrument used was the questionnaire proposed by the National Secretariat for Drug Policy (SENAD) for the I National Survey on the use of alcohol and other drugs among university students of the 27 Brazilian Capitals. Statistical Package for Social Science - SPSS 22 was used to analyze the data. The results showed a predominance of females, between 18 and 24 years of age, Evangelical / Protestant religion, socioeconomic class B and unmarried individuals. Regarding alcohol use, 85.6% reported lifetime use, 75.7% in the year and 62.3% in the month. 61.5% reported drinking in binge in the year and 46.8% in the month. As for tobacco, 36% reported use in life, 25.7% in the year and 20.9% in the month. Not having religion and missing classes were positively associated with binge in the year. Students who have already taken a ride with an alcoholic driver or the driver at the time have a greater chance of drinking in binge in the year and the month. Not having religion, too, was positively associated with tobacco, both for use in life and in the year. The results obtained allowed to know the profile of alcohol and tobacco use and its associated factors in the studied population, allowing to awaken in the academic community the need to include and / or extend the approach of the subject in the university curriculum of the course and to implement preventive actions misuse of these two substances.